Effect of Service Quality on Customer Satisfaction Through Brand Experience and Brand Awareness in Postal and Delivery Services - Vigory Gloriman Manalu; Ilham Akbar (Universitas Kuningan, 2019)
E-Commerce in Indonesia is increasing very fast compared to buying and selling activities in the digital world. It is noted that there are numbers of e-commerce that are growing rapidly in Indonesia, namely Lazada, Tokopedia, Shopee, BukaLapak and many others. With the development of e-commerce, the businessmen must be able to send their messages to customers well. There are several postal and delivery services companies in Indonesia, namely JNE, JnT, Pos Indonesia, Tiki and others. The purpose of conducting this research is to be able to provide input to the parties engaged in the field of postal and delivery services in order to find out what can affect customer satisfaction and increase its influence. the relationship between service quality on consumer satisfaction has no significant effect (H1 not supported), the relationship between service quality on brand experience has a positive and significant effect (H2 supported), the relationship between service quality on the brand. awareness has a positive and significant effect (H3 Supported), the relationship between brand experience on consumer satisfaction has a positive and significant effect (H4 supported), the relationship between brand awareness on consumer satisfaction has a positive and significant effect on (H5 supported)